Evaluasi Implementasi Otomasi Proses Dumping Material Panas dan Implikasinya terhadap Strategi B2B pada Industri Kimia - Prasetya, Prita; Handayani, Aniek Sri (Jurnal Informasi, Sains dan Teknologi, 2026)
Hot material dumping in the chemical industry is an important process stage that affects occupational safety, process stability, and product quality reliability. In manual processes, dumping activities may cause variation because they are influenced by operator condition, pouring angle, work speed, and exposure to hot materials. This study aims to analyze the consistency of the hot material dumping process and formulate a B2B strategy based on process reliability. The research method uses a descriptive-quantitative case study approach with data from 20 batches, analyzed through three indicators: dumping time, pouring flow stability, and material temperature change or ΔT. The data were primary data obtained directly through field observation, production-process documentation, and recording of process parameters; journal literature was used only as the theoretical and interpretive basis. The results show that the automated process provides more consistent performance than the manual process. The average dumping time decreased from 49.14 seconds to 30.18 seconds, the coefficient of variation for dumping time decreased from 12.44% to 1.36%, the pouring flow stability score increased from 2.55 to 4.70, and the average material ΔT decreased from 15.26°C to 8.16°C. These findings indicate that automation can improve process regularity, reduce variation between batches, and maintain material conditions in a more controlled manner. This process consistency can serve as the basis for a B2B strategy based on process reliability, emphasizing process reliability, production safety, quality consistency, and data-based evidence as key values in building industrial customer trust.